Ethnobiology of corals and coral reefs - Narchi, Nemer; Price, Lisa Leimar (Ethnobiology, 2015)
This book explores the ethnobiology of corals by examining the various ways in which humans, past and present, have exploited and taken care of coral and coralline habitats.  This book will bring the educated general audience closer to corals by exploring the various circumstances of human-coral coexistence by providing scientifically sound and jargon-free perspectives and experiences from across the globe. Corals are a vital part of the marine environment since they promote and sustain marine and global biodiversity while providing numerous other environmental and cultural services. Countless valuable coral conservation efforts are published in academic and general audience venues on a daily basis. However relevant, few of these reports show a direct, deeper understanding of the intimate relationship between people and corals throughout the world's societies. Ethnobiology of Corals and Coral Reefs establishes an intimate bond between the audience and the wonder of corals and their importance to humankind.